ANALISIS KOMPETENSI GURU DALAM MENGEMBANGKAN MINAT BELAJAR SISWA SDN NAPIS 4 BOJONEGORO - Binta Fathul Khorid; Widya Trio Pangestu; Yes Matheos Lasarus Malaikosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The purpose of this research is to determine the competence of teachers in developing student interest in learning at SDN Napis 4 Bojonegoro and to find out the obstacles faced by teachers in developing student interest in learning at SDN Napis 4 Bojonegoro. This research is a qualitative method using a qualitative descriptive approach. This research was conducted at SDN Napis 4 Bojonegoro, with a research time of three months. The targets of this study were all classes at SDN Napis 4 Bojonegoro and the targets in this study were all class teachers, all students, and all guardians of students at SDN Napis 4 Bojonegoro. The method of data collection is done by interview, observation, and documentation. There are several stages of data analysis in this study, namely data reduction, data display, and also drawing conclusions. The results of the research obtained are that the competence of teachers at SDN Napis 4 Bojonegoro is quite qualified. Based on the data obtained through both primary and secondary data, it can be concluded that students' interest in learning is good because it is influenced by a supportive environment and adequate teacher competence. This can be seen by the enthusiasm of the students in carrying out learning activities. Some of the ways that teachers do are by providing varied learning models, giving gifts and praise, and also studying the characteristics of students in learning.